2018
DOI: 10.1111/ibi.12618
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in the gut microbiota of wild House Sparrow nestlings

Abstract: Here, we document the development of the House Sparrow Passer domesticus gut microbiota for the benefit of future ecological and evolutionary studies in this widely used avian system. We collected and inventoried luminal and mucosal samples from the distal guts of nestling House Sparrows between 3 and 12 days of age, and also collected similar samples from adult birds. Luminal bacterial community membership and structure differed significantly between nestlings and adults. The relative abundance of Proteobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 46 publications
6
30
2
Order By: Relevance
“…Firmicutes, which is consistent with what was previously reported for House sparrows (Kohl et al, 2019;Mirón et al, 2014); however, we found higher relative abundance of Proteobacteria in samples stored dried. This result suggests that consideration should be given to differences in abundance at certain taxonomic levels that have undergone this type of storage, particularly those involving Proteobacteria and Actinobacteria which are able to grow at a range of temperatures (Weese and Jalali, 2014).…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…Firmicutes, which is consistent with what was previously reported for House sparrows (Kohl et al, 2019;Mirón et al, 2014); however, we found higher relative abundance of Proteobacteria in samples stored dried. This result suggests that consideration should be given to differences in abundance at certain taxonomic levels that have undergone this type of storage, particularly those involving Proteobacteria and Actinobacteria which are able to grow at a range of temperatures (Weese and Jalali, 2014).…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…Nearly 15% of hummingbird species are threatened or endangered, so understanding drivers of health and population dynamics may help conservation efforts. Avian microbial associates are just beginning to be studied in depth [18,20,21], and little is known about microbiome assembly in free-ranging birds or its association with avian health. In hummingbirds, some microorganisms have been linked with disease and mortality [22][23][24], while other microbes may be beneficial [21,25], particularly considering the birds' high-sugar diet [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In birds, studies examining age-related changes in gut microbial diversity are limited and show conflicting results, potentially due to differences in parental and environmental transmission of microbes across species (Dewar et al, 2017;Godoy-Vitorino et al, 2010;Grond, Lanctot, Jumpponen, & Sandercock, 2017;van Dongen et al, 2013;Yin et al, 2010). For example, older nestlings of great tits (Parus major) had lower cloacal microbial diversity than younger nestlings (Teyssier, Lens, Matthysen, & White, 2018), while the opposite was found in tree swallows (Tachycineta bicolor; Mills, Lombardo, & Thorpe, 1999), and in house sparrows (Passer domesticus) age did not have any effect on microbial diversity or community structure (Kohl, Brun, Caviedes-Vidal, & Karasov, 2019). In turkeys (Meleagris gallopavo) it has been found that gut microbial diversity initially increases and then subsequently decreases during development (Danzeisen et al, 2015;Wilkinson et al, 2017), while in chickens (Gallus gallus) there is often a successional increase in diversity with age (Ballou et al, 2016;Lu et al, 2003;Oakley et al, 2014;van der Wielen, Keuzenkamp, Lipman, van Knapen, & Biesterveld, 2002).…”
mentioning
confidence: 99%